2016
DOI: 10.1177/2048004016682177
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of abdominal aortic aneurysm calcification by means of variation of high-sensitivity C-reactive protein

Abstract: ObjectiveAbdominal aortic aneurysms are a major cause of death in developed countries, and thrombus and calcification of the aneurysm have been linked to increased complications. This study was conducted in order to identify the biochemical marker associated to the presence of intraluminal thrombus or calcification progression of the aneurysm.DesignSeveral clinical laboratory parameters were measured in patients with abdominal aortic aneurysms, in particular those already demonstrated to be related to the path… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
9
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 35 publications
0
9
0
Order By: Relevance
“…Lack of biomarkers for risk stratification of patients with AAA impedes development of novel personalized therapies and interventions since, in every patient with a not-yet “surgical” AAA, there are no clear predictors of a fast or slow progression of its own, AAA; that is, the best interval between a radiological check and the next step is not defined. Different authors have suggested a link between risk factors such as smoking history, obesity, glucose tolerance, dyslipidemia, chronic obstructive pulmonary disease, and renal failure and cardiovascular morbidity and mortality, together with some biomarkers such as RBC indices, WBC counts with differentials, platelet counts and neutrophil-to-lymphocyte ratio (NLR), and platelet-to-lymphocyte ratio (PLR), while no evidence exists in the literature about a possible association between AAA calcification and cell blood count (CBC) parameter even if it is a simple economic and extensively used basic hematological test [ 14 18 ]. The aim of our study is to evaluate if classical risk factor and biomarkers associated with AAA [ 14 , 15 ] can be associated with AAA calcification grade since an accessible and cost-effective measure such as a blood test predicting subsequent AAA progression in calcification could be used to rule in and/or rule out patients for more expensive MR and CT angiography, with benefit for patients and caregivers and with important reduction of cost.…”
Section: Introductionmentioning
confidence: 99%
“…Lack of biomarkers for risk stratification of patients with AAA impedes development of novel personalized therapies and interventions since, in every patient with a not-yet “surgical” AAA, there are no clear predictors of a fast or slow progression of its own, AAA; that is, the best interval between a radiological check and the next step is not defined. Different authors have suggested a link between risk factors such as smoking history, obesity, glucose tolerance, dyslipidemia, chronic obstructive pulmonary disease, and renal failure and cardiovascular morbidity and mortality, together with some biomarkers such as RBC indices, WBC counts with differentials, platelet counts and neutrophil-to-lymphocyte ratio (NLR), and platelet-to-lymphocyte ratio (PLR), while no evidence exists in the literature about a possible association between AAA calcification and cell blood count (CBC) parameter even if it is a simple economic and extensively used basic hematological test [ 14 18 ]. The aim of our study is to evaluate if classical risk factor and biomarkers associated with AAA [ 14 , 15 ] can be associated with AAA calcification grade since an accessible and cost-effective measure such as a blood test predicting subsequent AAA progression in calcification could be used to rule in and/or rule out patients for more expensive MR and CT angiography, with benefit for patients and caregivers and with important reduction of cost.…”
Section: Introductionmentioning
confidence: 99%
“…CRP is mainly expressed by hepatocytes, and its synthesis is regulated at the posttranscriptional level by cytokines, mainly by IL-6 with a synergic effect of IL-1 [ 13 ]. CRP can also be produced locally in atherosclerotic lesions [ 33 ]. A study by De Haro et al [ 34 ] showed that patients with symptomatic and ruptured aneurysms had elevated serum CRP compared with patients with asymptomatic AAA.…”
Section: Discussionmentioning
confidence: 99%
“…The study is conformed to the ethical guidelines of the "World Medical Association Declaration of Helsinki -Ethical Principles for Medical Research Involving Human Subjects" adopted by the 18th World Medical Association General Assembly, Helsinki, Finland, June 1964, and revised in Tokyo in 2004. Institutional ethic committees approved the study, and all patients provided a written informed consent (Ethics Committee of ASST Spedali Civili di Brescia, approval reference number: 1353) [ 7 ]. Participants did not receive any form of financial compensation.…”
Section: Patients and Specimensmentioning
confidence: 99%